Cross‐resistance relationships of the sulfoximine insecticide sulfoxaflor with neonicotinoids and other insecticides in the whiteflies Bemisia tabaci and Trialeurodes vaporariorum. Issue 7 (30th November 2012) - Longhurst, Christopher; Babcock, Jonathan M; Denholm, Ian; Gorman, Kevin; Thomas, James D; Sparks, Thomas C
Abstract BACKGROUND Insecticides are important tools for managing damaging insect pests. Compounds that are effective against pests such as the whiteflies Bemisia tabaci and Trialeurodes vaporariorum, which show resistance to a range of insecticidal modes of action (MOA), have particular value as components of resistance management programmes. The sulfoximine insecticides are chemically unique as the first to incorporate a sulfoximine functional group. Sulfoxaflor is the first sulfoximine compound under commercial development for the control of sap‐feeding insects. Its cross‐resistance relationships were investigated by comparing the responses of field‐collected strains with those of insecticide‐susceptible laboratory strains of B. tabaci and T. vaporariorum. RESULTS Sulfoxaflor exhibited very low (less than threefold) resistance ratios (RR) when tested against strains of B. tabaci that produced RR of up to 1000‐fold to imidacloprid and cross‐resistance to other neonicotinoid insecticides. Similarly, sulfoxaflor was not cross‐resistant in a strain of B. tabaci exhibiting resistance to a pyrethroid (deltamethrin) and an organophosphate (profenophos). No cross‐resistance was observed between sulfoxaflor and imidacloprid in T. vaporariorum. One population of the three field strains tested showed slightly reduced susceptibility to sufloxaflor with an RR of 4.17. By comparison, this same population exhibited an RR of more than 23.8‐fold for imidacloprid relative to the susceptible population. CONCLUSION In spite of sharing a target site with neonicotinoids (the nicotinic acetylcholine receptor), sulfoxaflor was largely unaffected by existing cases of neonicotinoid resistance in B. tabaci and T. vaporariorum. Neonicotinoid resistance mechanisms in these whitefly species are known to be primarily based on enhanced detoxification of insecticide. This lack of cross‐resistance indicates that sulfoxaflor is a valuable new tool for the management of sap‐feeding pests already resistant to established insecticide groups.© 2012 Society of Chemical Industry